URBAN GREEN INFRASTRUCTURE FOR CLIMATE RESILIENCE: A REVIEW - Tauhid, Fahmyddin Araaf (Nature: National Academic Journal of Architecture, 2018)
Abstract: As the climate change affectingon coastal cities by increasing the intensity and frequency of climate related disasters such as flooding, sea level rise, drought etc., the need to explore other urban infrastructure strategies than conventional one is required. This alternative not only mitigate the impacts but also improve the urban climate resilience. In line with it, green infrastructure/GI can be sustainable alternative in that way combine with gray infrastructure. Therefore, this paper reviews the concept of GI to advance the urban resilience associated with climate related disasters. Some strategies based on the current literature and projects are also recommended including managing flood risk, building resiliency to drought, reducing the urban heat island effect, lowering building energy demands, improving coastal resiliency, and reducing energy needed to manage water. Key words: Green Infrastructure, Climate Resilience, Urban Resilience, Sustainability, Flood, Drought,Sea level Rise. <!--[if !supportAnnotations]--> <!--[endif]-->